2012
DOI: 10.33762/bvetr.2012.54771
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Enterotoxin ( Cyt K ) Gene and Antimicrobial Susceptibility of Bacillus Cereus Isolates From Milk and Milk Products

Abstract: Two hundred twenty seven samples of milk, soft cheese, curls cheese and yogurt were taken to isolate B. cereus. The percentage of these bacteria was 32.7 %, 16.6 %, 18 % and 26% in milk, soft cheese, curls cheese and yogurt, respectively. Mannitol egg-yolk agar (MYP) supplemented with polymyxin B sulfate is used for isolation. Identification of the isolates was done by biochemical tests. Screening of isolates by polymerase chain reaction ( PCR ) revealed the presence of diarrheal toxin cyt K gene in 87.09 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In Poland, B. cereus strains were isolated from 14.1% of the mould cheese samples (Berthold ), while in Iraq, the percentage of these bacteria was 16.6% and 18% in soft cheese and curled cheese, respectively (Khudor et al . ). In the present study, the incidence of B. cereus in ice cream samples was 20%.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In Poland, B. cereus strains were isolated from 14.1% of the mould cheese samples (Berthold ), while in Iraq, the percentage of these bacteria was 16.6% and 18% in soft cheese and curled cheese, respectively (Khudor et al . ). In the present study, the incidence of B. cereus in ice cream samples was 20%.…”
Section: Discussionmentioning
confidence: 97%
“…Khudor et al . () reported that 32.7% of raw milk samples examined in Iraq were contaminated with B. cereus . The prevalence of B. cereus in raw milk samples varied from 6.34 to 75.3% in Turkey (Gundogan and Arik ; Dikbas ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations